PELATIHAN DAN PENDAMPINGAN IDENTIFIKASI MASALAH DAN STRATEGI PENGELOLAAN ORGANISASI YANG BAIK BAGI IKATAN KELUARGA BESAR BIINMAFO, TTU, NTT, DI JAWA TIMUR - Ninuk Muljani; Antonius Yuniarto; Daniel Tulasi; Sri Yunan Budiarsi; Dominicus Wahyu Pradana (Nindikayla Institute, 2022)
This community service activity aims to help the BIINMAFO organization grow well in East Java. The form of service is in the form of training, assistance for BIINMAFO administrators in East Java. The activity was carried out for two consecutive days involving 15 core BIINMAFO administrators. The topics of the study presented were Organizational Philosophy, Organizational Governance, and Identification of Organizational Problems to find alternative solutions that were useful for the advancement of BIINMAFO. The result of this activity is that BIINMAFO's core management is able to map problems, grow awareness of the organization's philosophy, and how to design good governance for BIINMAFO. Of course, it is not easy to realize good organizational governance. A follow-up program is needed as an effort to create a good BIINMAFO organization in East Java.